Does genetic personality and parenting style influence on student character building - Masduki Asbari; Laksmi Mayesti Wijayanti; Choi Chi Hyun; Agus Purwanto (International Journal of Evaluation and Research in Education (IJERE), 2022)
Character building is very important to become a key educational mainstream in Indonesia for formal, non-formal and informal setting. There are several factor that influence student character building, namely parenting style and genetic personality. The purpose of this research is to identify the influence of parenting style and genetic personality to student’s character building.. This research is a correlational study using survey and quantitative method. The population in this study were parents who have school-age children and their children have genetic personality test (STIFIn test) in Indonesia. Data collection was carried out by simple random sampling via electronic. The returned and valid questionnaire results were 625 samples. Data collection technique is using questionnaire with likert scale. The instrument of this study is a modification from Parenting Style Questionnaire (PSQ) Robinson et al. (1995) and Roman et al. (2015). To measure the genetic personality, the instrument is adapted from STIFIn Personality Concept (Poniman & Mangussara, 2013). Another instrument used to measure student character building is an adaptation from Poniman et. Al (2014). Analysis from this study is using SEM (Structural Equation Model) with SmartPLS version 3.0 as a statistic tools. The result of this study argued that parenting style and genetic personality have a positive influence and significantly contributed to student character building. This study also reinforces the theory that student character building is significantly affected by genetic personality and parenting style. Finally, it is recommended that parents should improve the quality of parenting and need to know their chlid’s genetic personality by personality test (e.g., STIFIn Test).